PHYSICAL CHEMICAL CHARACTERISTICS OF JELLY CANDY HYDROXYAPATITE FROM YELLOWFIN TUNA FISH BONE WASTE (THUNNUS ALBACARES) - izar, Shaflina; Faisal , Hendri; Khairunisah , Dinda; Nasution , Rizka Hasmi (Journal for Technology and Science, 2024)
Introduction:  jelly candy is a soft-textured candy that is generally given to children with the aim of optimal growth and development with calcium. Hydroxyapatite content in the preparation of jelly candy can be achieved by using the addition of ingredients containing calcium that come from nature, one of which is by using yellowfin tuna fish bone meal as the main ingredient to increase the calcium content in  jelly candy. The aim of the research was to find out that hydroxyapatite from yellowfin tuna bones (Thunnus albacares) can be formulated in the form of jelly candy to determine the hydroxyapatite of yellowfin tuna bones (Thunnus albacares) contains calcium. The research method uses laboratory experimental research. The treatment in this research is a dosage formulation of jelly candy from the bones of yellowfin tuna (Thunnus albacares). The results showed that the higher the concentration of yellowfin tuna bone meal (Thunnus albacares) the higher the calcium levels. The conclusion of this research is that hydroxyapatite of yellowfin tuna bones (Thunnus albacares) can be formulated into dosage forms jelly candy. Yellowfin tuna bone hydroxyapatite (Thunnus albacares) contains calcium and the highest calcium content is in F3 (7%) with a value of 39.3%.